Effect of female literacy rate and education on infant mortality in Peru, 2001–2022 - Julio Cesar Quispe Mamani; Santotomas Licimaco Aguilar Pinto; Amira Carpio Maraza; Yethy Melixa Poma Palma; Lucas Ponce Quispe; Nelly Beatriz Quispe Maquera; Balbina Esperanza Cutipa Quilca; Betsy Quispe Quispe; Paola Huarca Flores; Dominga Asunción Calcina Álvarez; Lycet Maria Caceres Bustinza (Frontiers in Public Health)
IntroductionInfant mortality is one of the most sensitive indicators of a country’s social and health development. Despite advances in public policies aimed at maternal and child health, significant challenges remain in sustainably reducing mortality rates among children under one year of age. The objective of this study was to analyze the impact of women’s literacy rate and educational level on infant mortality across the 24 departments and the constitutional province of Peru between 2001 and 2022.Materials and methodsData provided by the National Institute of Statistics and Informatics (INEI) were used, and a statistical analysis was conducted to explore the relationship between female literacy rate, educational attainment, and infant mortality across different regions of the country. A panel data model was employed, allowing for the assessment of both temporal variations and regional differences.ResultsThe findings reveal a significant and inverse relationship between women’s educational level— as measured by literacy rate and average years of schooling—and the infant mortality rate in Peru from 2001 to 2022. Higher levels of female education are associated with lower infant mortality, highlighting the central role of education as a determinant of child health. Furthermore, substantial regional disparities persist, particularly in rural and impoverished areas, where educational levels are lower and infant mortality rates are higher.Discussion and conclusionsThese results underscore the need for comprehensive public policies that improve both access to and the quality of education, strengthen infrastructure in health and education, and prioritize targeted interventions to reduce territorial gaps. A multisectoral and inclusive approach is essential to achieve sustainable improvements in child health indicators and promote social equity in the country.